Peran Otoritas Jasa Keuangan Terhadap Perlindungan Kosumen Generasi Z Sebagai Pengguna Pinjaman Online: Penelitian - Ghinaa Afiifah; Anna Triningsih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The development of financial technology has encouraged the increasing use of online loan services, especially among Generation Z. The ease of access and the fast disbursement process of funds make online loans an alternative to fulfilling financial needs, but on the other hand it causes various problems, such as the rampant illegal online loans, unreasonable interest, unethical billing, and misuse of consumer personal data. This research aims to analyze the role and implications of the supervision of the Financial Services Authority (OJK) towards the protection of Generation Z consumers as online loan users. The research method used is normative legal research with a normative legal approach through literature studies on relevant laws and regulations and literature. The research results show that OJK has the authority to attribute it based on Law Number 21 of 2011 to regulate, supervise, and protect consumers in the financial services sector, including fintech lending services. Although the supervision of OJK has given a positive impact in the form of increased compliance with legal online loan providers, consumer protection has not been fully optimal due to limited authority against illegal online loans, low financial literacy of the community, and surveillance challenges in the digital era. Therefore, it is necessary to strengthen regulation, improve coordination between.